What Makes Anti-Racist Pedagogy in Teacher Education Difficult? Three Popular Ideological Assumptions - St. Denis, Verna; Schick, Carol (Alberta Journal of Educational Research, 2003)
This article arises from the teaching observations and struggles of two anti-racist educators who co-developed and taught a required cross-cultural education course for predominantly white-identified preservice teachers in a Canadian prairie context. The article identifies three common ideological assumptions about the production of inequality frequently held by these students: race does not matter; everyone has equal opportunity; and through individual acts and good intentions one can secure innocence as well as superiority. These preservice teachers are required to examine the dominant identifications and power relations through which they are produced and unwittingly implicated in reproducing the status quo.